Mass Determination Algorithms Using High Energy Digital Radiography; Advanced Materials Research; Vol. 1085 : Prospects of Fundamental Sciences Development (PFSD-2014) - Osipov S. P. Sergey Pavlovich; Klimenov V. A. Vasily Aleksandrovich; Osipov O. S. Oleg Sergeevich; Samigullin V.'dan D.; Stein A. M. Aleksandr Mikhailovich (Mathematical Methods in Materials Science, 2015)
Title screen